The Effects of Preoperative Coronary Collateral Circulation on Cardiac-Related Events after Coronary Artery Bypass Graft Surgery - Güngör,Hasan (2021)
Abstract Introduction: This study aimed to evaluate the effects of coronary collateral circulation (CCC) in patients who had undergone coronary artery bypass grafting (CABG). Methods: A total of 127 patients who had undergone CABG (2011-2013) were enrolled into this study and follow-up was obtained by phone contact. Patients were categorized into two groups according to preoperative CCC using the Rentrop method. Percutaneous coronary intervention (PCI), recurrent myocardial infarction (MI), stroke, heart failure (HF), and mortality rates were compared between groups. Clinical outcome was defined as combined end point including death, PCI, recurrent MI, stroke, and HF. Results: Sixty-two of 127 patients had poor CCC and 65 had good CCC. There were no differences in terms of PCI, recurrent MI, and HF between the groups. Stroke (seven of 62 [11.3%] and one of 65 [1.5%], P=0.026) and mortality (19 of 62 [30.6%] and 10 of 65 [15.4%], P=0.033) rates were significantly higher in poor CCC group than in good CCC group. In Kaplan-Meier analysis, survival time was not statistically different between the groups. Presence of poor CCC resulted in a significantly higher combined end point incidence (P=0.011). Conclusion: Stroke, mortality rates, and combined end point incidence were significantly higher in poor CCC patients than in the good CCC group.